Safety and security engineering IV - International Conference on Safety and Security Engineering (4th : 2011 : Antwerp); Guarascio, M. (Massimo); Wessex Institute of Technology; Universitaire Instelling Antwerpen; Universit d̉egli studi di Roma "La Sapienza" (Southampton : WIT Press)
Includes bibliographical references and index